2015
DOI: 10.1515/fascmath-2015-0020
|View full text |Cite
|
Sign up to set email alerts
|

Some New Classes of Generalized Hermite-Based Apostol-Euler and Apostol-Genocchi Polynomials

Abstract: In this paper, we introduce a new class of generalized Apostol-Hermite-Euler polynomials and Apostol-Hermite-Genocchi polynomials and derive some implicit summation formulae by applying the generating functions. These results extend some known summations and identities of generalized Hermite-Euler polynomials studied by Dattoli et al, Kurt and Pathan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 16 publications
3
10
0
Order By: Relevance
“…These results extend some known summations and identities of generalized Hermite multipoly-Bernoulli numbers and polynomials of the second kind studied by Qi et al [11], Dattoli et al [5], Khan [7] and Pathan and Khan [9,10].…”
Section: It Is Easily Seen From Definition (1) Thatsupporting
confidence: 86%
See 1 more Smart Citation
“…These results extend some known summations and identities of generalized Hermite multipoly-Bernoulli numbers and polynomials of the second kind studied by Qi et al [11], Dattoli et al [5], Khan [7] and Pathan and Khan [9,10].…”
Section: It Is Easily Seen From Definition (1) Thatsupporting
confidence: 86%
“…n (x) are called the higher order Bernoulli polynomials of the first kind given by the generating function (see [7,8,9,10]):…”
Section: It Is Easily Seen From Definition (1) Thatmentioning
confidence: 99%
“…Replacing n by n-p in the above equation and comparing the coefficients of t n , we get the result (2.11). x y the same considerations as developed for the ordinary Hermite and related polynomials in Khan et al [21] and Hermite-Bernoulli polynomials in Pathan and Khan [29][30][31][32][33][34]…”
Section: Hermite Poly-bernoulli Numbers and Polynomials Of The Secondmentioning
confidence: 99%
“…and the Stirling number of the second kind is defined by generating function to be ( ) Recently many mathematicians have studied the symmetric identities on some special polynomials see for details [29][30][31][32][33][34]43,44]. Some of mathematicians also investigated some applications of poly-Bernoulli numbers and polynomials of the second kind cf.…”
Section: Introductionmentioning
confidence: 99%
“…Problems of this type arise, for example, in the computation of the higher-order moments of a distribution or to evaluate transition matrix elements in quantum mechanics. In [7], [8], [9], [19], [20], [21], [22], it has been shown that the summation formulae of special functions, encountered in applications ranging from electromagnetic process to combinatorics can be written in terms of Hermite polynomials of more than one variable.…”
Section: Introductionmentioning
confidence: 99%